How to kill a unicorn : how the world's hottest innovation factory builds bold ideas that make it to market - Payne, Mark (New York : Crown Business, 2014)
The president of innovation consultancy firm Fahrenheit 212 describes the company's methodology for combining'magic' with money to bring to market unique products and ideas that will transform a company's business and growth.
Includes index.
Text in English.
Keywords: Creative ability in business; New products -- Management; Marketing